Volcanostratigraphy of Krakatoa Islands, South Lampung District, Lampung Province. Issue 1 (November 2020) - Ismail, Taufik; Abdurrachman, Mirzam; Rizal, Yan; Hardjawidjaksana, Kumala
Abstract: The research area is within the territory of Nature Preserve and Marine Preserve region of Krakatoa Islands, South Lampung District, Lampung Province. The study aims to determine the surface geological, mapped on a scale of 1: 20, 000, and to determine the geological history that forms the Krakatoa Islands. Volcanostratigraphy is made by combined from literature studied, shoreline analysis, petrographic analysis and field observation. From these results, it is poured into a map of geological outcrops, maps of volcanostratigraphy profiles, geological maps and geological sections. Volcanostratigraphy on the research area is divided into 30 rock units that consists of 22 lava, 8 pyroclastic and allvuial. Geological structure that developed in the research area in the form of secondary structure that is crater and caldera, and the primary structure that is sheeting joinnt, columnar joint, vesicular and autobreccia. New and detailed geological map of Krakatoa volcano is presented.